ANALYZING SENTENCE STRUCTURE: PRINCIPAL, SECONDARY AND TERTIARY COMPONE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theory of parts of the sentence, focusing on itsthree main components: principal, secondary, and tertiary parts. The principal parts subjectand predicate—form the structural foundation of sentences, while secondary parts such asobjects, complements, and adverbial modifiers add depth and detail. The article highlightsthe challenges posed by tertiary elements like appositions, interjections, and parentheticalexpressions, which often defy strict categorization due to their fluidity and contextualsignificance. Beyond grammatical analysis, the article examines the broader implicationsof this theory for syntax, semantics, pedagogy, and computational linguistics.